An Adaptable Interface Conditioning Circuit Based on Triboelectric Nanogenerators for Self-Powered Sensors - Hu, Yongshan (Micromachines (Basel), 2018)
In order to solve the limited life problem of typical battery power supply, a self-powered method that is based on the environmental energy harvesting has emerged as an amazing power supply approach. The Tribo-electric-Nano-generator (TENG) has been widely studied because of its high efficiency, low fabrication cost, and high output voltage. However, low output power conversion efficiency has restricted its practical application because of its own extremely high output impedance. In order to match the high output impedance of TENG and increase the output power, this paper presents an adaptable interface conditioning circuit, which is composed of an impedance matching circuit, a synchronous rectifier bridge, a control circuit, and an energy storage device. In the impedance matching circuit, the energy loss of coupling inductance could be reduced by using the bi-directional switch to increase the frequency, and impedance matching circuit can be used to increase the output efficiency of TENG. Experimental results show that, in about 3.6 s, the storing capacitor voltage was basically stable at 5.5 V by using the proposed adapted interface conditioning circuit in this paper. The charging efficiency has increased by 50%.